E-Modul Berbasis Project Based Learning dan Design Thingking Method pada Pembelajaran Kewirausahaan - Fransisca Rahcmawati Indira (Jurnal Pendidikan Ekonomi, 2023)
This study aims to identify the effectiveness of implementing the Project Based Learning Model and Design Thinking Method E-Module to improve students' Critical Thinking Skills and identify the Project Based Learning Model and Design Thinking Method development design for entrepreneurship learning. This type of research uses a literature study approach. The method used in writing this article uses the literature review method, the source of which is obtained from the Google Scholar website with the last five years published, namely 2018-2022, from the articles obtained, 20 articles were selected that were most relevant to this research topic. The data collection technique in this study was to collect data using various scientific articles relevant to the research topic. The results of the analysis of various literature reviews show that the use of E-Modules based on Project Based Learning Models and Design Thinking Methods is effective for increasing students' critical thinking skills. Then the researchers succeeded in creating an entrepreneurial learning design through a collaboration of the Project Based Learning Model and Design Thinking Method which consisted of 8 Phases.